Design and Analysis of a Three-Phase High-Frequency Transformer for Three-Phase Bidirectional Isolated DC-DC Converter Using Superposition Theorem - Dira Y.S.; Ramli A.Q.; Ungku Amirulddin U.A.; Tan N.M.L.; Buticchi G. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Battery energy storage systems based on bidirectional isolated DC-DC converters (BIDCs) have been employed to level the output power of intermittent renewable energy generators and to supply power to electric vehicles. Moreover, BIDCs use high-frequency transformers (HFTs) to achieve voltage matching and galvanic isolation. Various studies have recently been conducted using soft magnetic materials, such as nanocrystalline, amorphous solids, and ferrite, to develop more compact and effective transformers with superior power densities. The HFTs in three-phase BIDCs are composed of three magnetic cores. However, this leads to low power density and high cost. Besides, the three-phase (3P) ferrite core has not been investigated for high-power converters such as 3P-BIDCs. This paper presents the design and development of a 3P-EE ferrite magnetic core for 3P-BIDCs. The area product design method was used to determine the core and winding design. The paper also proposes the use of the superposition theorem in conducting a magnetic circuit analysis to predict the flux density and magnetising inductance of the transformer core. Moreover, the use of the superposition theorem allowed the required air-gap length for balancing the distribution of flux density and magnetizing inductance in the transformer core to be determined. The balanced flux distribution and magnetizing inductance resulted in a uniform core loss and temperature in the transformer. This paper also presents the experimental results of the designed HFT operated in a 300-V, 3-kW 3P-BIDC. The experimental results showed that the proposed HFT achieved a balanced flux density and magnetizing inductance with a high power density and low cost. Moreover, the transformer performed at a maximum efficiency of 98.67%, with a decrease of 3.33 C in the overall temperature of the transformer as compared to the transformer without air gaps. ? 2024 by the authors.